XVIII. Research on the Export Trade Potential of Chinese Agricultural Products With Belt and Road Countries - Wang, Weilong (The Impact of Digital Economy on One Belt One Road Initiative, 2025)
This paper focuses on the trade potential of agricultural products, exploring the development and application of the gravity model for measuring trade potential from both domestic and international perspectives. Scholars commonly use GDP, population, and spatial distance as primary indicators. From the perspective of the agricultural product trade potential, the paper analyses agricultural trade research between Belt and Road countries and other regions. It focuses primarily on measuring trade potential from China's perspective, with limited studies on other countries' trade potential with China. The analysis often involves comparative advantage and complementarity indicators, with limited use of the Trade Potential Index (TPI).